ANALYSIS OF FACTORS AFFECTING REGIONAL ORIGINAL REVENUE (PAD) IN BADUNG REGENCY - Gusti Ayu Putri Sagita Maharani; Ni Luh Karmini (CV. Adiba Aisha Amira, 2025)
Regional Original Revenue (PAD) is one of the main indicators of a region's financial independence in managing its local economy. This study aims to analyze the effect of the number of tourist visits, the number of restaurants, the number of accommodations, and the population size on the Regional Original Revenue (PAD) of Badung Regency. As the tourism hub of Bali Province, Badung Regency holds significant potential for increasing PAD through the tourism sector and its supporting industries. This research adopts a quantitative approach using multiple linear regression analysis and employs secondary time series data from 2009 to 2023, sourced from the Central Bureau of Statistics (BPS) and related institutions. The research results show that simultaneously, the variables of tourist visits, the number of restaurants, the number of accommodations, and the size of the population have a significant impact on the local revenue of Badung Regency. However, partially, only the number of restaurants and the population have a significant and positive effect on local revenue, while the number of tourist visits and accommodations do not have a statistically significant partial impact. These findings indicate that the increase in the number of restaurants has a more direct impact on local revenue compared to other variables. This study is expected to provide input for the local government of Badung Regency in formulating effective policies to increase local revenue with a focus on sectors that show statistically significant contributions. Additionally, this offers empirical insights into the simultaneous and partial contributions of these factors to regional income.